The role of endoscopic management and adjuvant topical therapy for upper tract urothelial cancer - Chien, Austin L.; Chua, Kevin J.; Doppalapudi, Sai Krishnaraya; Ghodoussipour, Saum (Frontiers in Urology, 2022)
Upper tract urothelial carcinoma (UTUC) has traditionally been managed with radical nephroureterectomy, and while this approach remains the gold standard for high-risk disease, endoscopic, kidney-sparing management has increasingly been adopted for low-risk disease as it preserves kidney function without compromising oncologic outcomes. Ureteroscopy and percutaneous renal access not only provide diagnoses by tumor visualization and biopsy, but also enable treatment with electrocautery or laser ablation. Several modalities exist for laser ablative treatments including neodymium:YAG, holmium:YAG, thulium:YAG, and combinations of the preceding. Furthermore, due to high recurrence rates after endoscopic management, adjuvant intracavitary instillation of various agents such as mitomycin C and bacillus Calmette-Guerin have been used given benefits seen in non-muscle invasive urothelial bladder cancer. Other formulations also being studied include gemcitabine, anthracyclines, and immunotherapies. More recently, Jelmyto, a mitomycin reverse thermal gel, has been developed to allow for adequate drug delivery time and potency since urine flow could otherwise dilute and washout topical therapy. In this article, the authors review techniques, indications, best practices, and areas of current investigation in endoscopic management and adjuvant topical therapy for UTUC.